Determining Center of Rotation and Scapular Notching in Reverse Total Shoulder Arthroplasty: A Reliability Study. Issue 2 (June 2015) - Bragg, William; Niu, Emily; Harris, Alex H. S.; Nguyen, Michael; Cheung, Emilie
Abstract : There is no widely recognized method of radiographic analysis of shoulders undergoing reverse total shoulder arthroplasty (RTSA). We aim to develop a reproducible method of comparing preoperative to postoperative changes in the glenohumeral center of rotation (COR) using digital radiographic evaluation. Four independent reviewers analyzed preoperative and postoperative radiographs in 29 consecutive patients undergoing RTSA. Preoperative radiographic parameters were medialization of the humeral head and distalization of the glenohumeral COR. Postoperative radiographs were evaluated for distalization of the glenoid COR. Presence of scapular notching was evaluated. Intraobserver and interobserver reliability was tested for all measurements. The mean medialization and distalization of the glenohumeral COR were 23 and 7 mm, respectively. There was variability in intrarater and interrater correlation coefficients for all measured parameters. Reliability was moderate for measurements of preoperative COR medialization and distalization. Reliability was slight for measurements of postoperative COR distalization and presence of scapular notching. Comparison of preoperative and postoperative measurements demonstrated a significant decrease in postoperative interrater reliability. There was no consistent trend related to years of training of the reviewer except with respect to postoperative COR distalization. We show that radiographic assessment of COR change from preoperative to postoperative is not reliable. Radiographic assessment of scapular notching is also not reliable. This study emphasizes the need for further refinement of methods of radiographic digital analysis of shoulders undergoing RTSA. Level of Evidence: Level IV—retrospective diagnostic study. See Instructions for Authors for a complete description of levels of evidence